IN VIVO ANTIOXIDANT ACTIVITY OF ETHANOLIC AND AQUEOUS EXTRACT OF POLYHERBAL FORMULATION IN DIABETES INDUCED RATS - AJAY MANDAL; P. JAGAN MOHAN REDDY (International Journal of Pharma and Bio Sciences, 2016)
Antioxidant activity of polyherbal formulation of aqueous and ethanolic extract of Ocimum sanctum, Withania somnifera, Gymnema sylvestre, Tinospora cordifolia, Phyllanthus emblica and Coleus forskohlii were carried out in the present study. Antioxidant potential was investigated using in vivo assay like SOD radical scavenging assay, CAT radical scavenging activity and MDA scavenging activity. Various Phyto constituents were identified in the above selected plant (after taxonomical screening) extracts were poly phenols, flavonoids, terpenoids, tannins, alkaloids. It is evident that terpenoids were stated to possess the scavenging properties against the free radicals. The presence of these Phytoconstituents in selected plants stimulated to assess the scavenging property against free radical.. After 7 days of treatment with Glibenclamide, Hot water extract of Polyherbal Formulation (200 mg/kg & 400 mg/kg) and Ethanolic extract of Polyherbal Formulation (200 mg/kg & 400 mg/kg) in treated groups were observed and it showed significant (P< 0.001) reduction in lipid peroxidation in tissue MDA levels and significantly (P< 0.001) increased the levels of SOD and CAT in diabetic rat liver, and this indicate the effective antioxidant property of the polyherbal formulation. This study forms a base of for drug discovery on natural antioxidant drugs.